Fluid loss does not explain coagulation activation during air travel - Schreijer, Anja J. M.; Cannegieter, Suzanne C.; Caramella, Marianna; Meijers, Joost C. M.; Krediet, Raymond T.; Simons, Ries M.; Rosendaal, Frits R. (Thrombosis and Haemostasis, 2008)
The mechanism of air travel-related venous thrombosis is unclear. Although immobility plays a pivotal role, other factors such as fluid loss may contribute. We investigated whether fluid loss occurred more in individuals with coagulation activation after air travel than in subjects without. As a secondary aim, we investigated whether fluid loss per se occurred during air travel. In this crossover study, 71 healthy volunteers were exposed to eight hours of air travel, eight hours immobilization in a cinema, and a daily-life control situation. Markers of fluid loss (haematocrit, serum osmolality and albumin) and of coagulation activation were measured before and after each exposure. The study included ll volunteers with and 55 volunteers without coagulation activation during the flight. The change in parameters of fluid loss was not different in volunteers with an activated clotting system from those without (difference between groups in haematocrit: −0.6%, 95% confidence interval [CI]: −1.9 to 0.6). On a group level, mean haematocrit values decreased during all three exposures. However, in some individuals it increased, which occurred in more participants during the flight (34%; 95% CI 22 to 46) than during the daily-life situation (l9%; 95% CI 10 to 28). These findings do not support the hypothesis that fluid loss contributes to thrombus formation during air travel.
Keywords: Venous thrombosis; hypercoagulability; air travel; fluid loss; dehydration